Learning Trajectory for Pre-Service Mathematics Teachers in Geometry through the Context of Bengkulu Conic-Section Batik Patterns - Ratnah Lestary; Febri Kristiani; Pika Merliza (Jurnal Inovasi Matematika, 2026)
The understanding of analytic geometry is often hindered by its abstract presentation and its disconnection from local contexts familiar to students. Therefore, this study designed a learning trajectory using conic section batik patterns rooted in Bengkulu’s cultural context. This served as a consolidation phase in learning conic sections and geometric transformations. The study used a design research methodology with three phases: preliminary design, teaching experiment, and retrospective analysis. The participants were mathematics education students enrolled in an Analytic Geometry course. The findings showed that the resulting learning trajectory has three interconnected learning pathways: conceptual exploration, validation through practice, and applicative project work. These pathways illustrate a progression of understanding, moving from procedural toward relational, representational, and applicative thinking. The conic section batik–based learning approach helped students connect elements and general equations of conic sections with visual representations using GeoGebra. It allowed them to apply these concepts in contextual batik designs.